Faktor Penentu Penghimpunan Dana Pihak Ketiga Bank Umum Syariah Periode 2015-2020 - Putri, Amelia; Suryani, Suryani; Risyanto, Havid (Jurnal Manajemen Bisnis dan Keuangan, 2022)
Third-Party Funds of Islamic Banks are money obtained by banks by the public. People who save money in banks are one of the sources used by banks to make loans to people in need. When third-party funds are collected, there are internal as well as external factors that play a role in how they are collected. This research is quantitative with a multiple linear regression analysis method. Quantitative data uses periodic data types. The results of the study indicate whether there is an influence on the collection of third-party funds, the equivalent rate partially has a bad effect, the BI 7-day reverse repo rate has no effect, inflation has a negative effect, and the number of offices has a positive effect. The variable equivalent rate, BI 7-day reverse repo rate, inflation, and the number of offices simultaneously have a good effect.